A Prospective Study of Auditory Functions in Patients Undergoing Dialysis - Ankush Pandit; Parth Makwana; Vaibhav Patel (Bengal Journal of Otolaryngology and Head Neck Surgery)
Introduction: Hearing loss, as a side effect of chronic renal failure (CRF), is ignored though the incidence of sensorineural hearing loss (SNHL) among CRF patients is considerably higher than in general population. The present study was conducted in this context as an attempt (i) To find out the occurrence of SNHL viz-a-viz severity of hearing impairment in CRF patients undergoing hemodialysis. (ii) To assess HL at different frequencies in CRF patients. (iii) To study correlation between severity of HL and demographic features. (iv) To assess the factors affecting HL in CRF patients.